Prophylactic antibiotic use for variceal bleeding in Child Class A cirrhosis: Scope for risk adaptive strategy - Fatima, Wajiha; Sarwar, Shahid; Sabir, Muhammad Ali; Rubab, Mishal; Munawar, Safa; Shehzad, Khurram (International Journal of Pathology, 2025)
Background: Acute variceal bleeding is one of the serious complications in patients with liver cirrhosis, significantly contributing to morbidity in this population. The current recommendations encourage universal antibiotic prophylaxis. However, its benefit in low-risk patients, especially those in early stage of cirrhosis, is still not well understood. The aim of this study was to evaluate the necessity of antibiotic prophylaxis in patients with compensated, Child-Pugh Class A cirrhosis.Methods: A study with a quasi-experimental design was carried out in Medical Unit 1 of Jinnah Hospital Lahore. This study involved 120 patients with early-stage cirrhosis (Child-Pugh A) who experienced acute variceal bleed. Patients with ascites, WBC >12×10³/µL, Child-Pugh B/C, hepatic encephalopathy, SBP, or hepatorenal syndrome were excluded. Two groups were formed from the study participants. Group A received intravenous ceftriaxone 1 gram daily, while Group B received a placebo. Outcomes included infection, hepatic encephalopathy, and mortality. Infection Probability Score (IPS) was calculated and predictive accuracy was evaluated using ROC curve analysis. Data analysis was carried out using SPSS v20.Results: Mean age was 57.4 ± 12.1 years; 58.3% were male. Baseline characteristics did not differ significantly between the groups. No significant difference was found in encephalopathy (2.5%), ascites (5%), transfusion (16.7%), fever (6.7%), or mortality (4.2%) between groups (p > 0.05). IPS was substantially elevated in patients who died (12.6 ± 3.4) versus survivors (8.2 ± 1.1), p < 0.001. IPS showed strong predictive value for mortality (AUC = 0.877). IPS >10 predicted mortality with 80% sensitivity, 93.9% specificity, and 99.1% NPV.Conclusion: Antibiotics for primary prophylaxis in Child Class A cirrhosis experiencing variceal bleed is not necessary and a risk adaptive strategy should be adopted. IPS may serve as a valuable tool in evaluating mortality risk associated with variceal bleeding.